Research the influence of excipients on the technological properties of captopril fast dissolving films - M. B. Demchuk; Yu. Ya. Melnyk; N. V. Malanchyk; T. A. Groshovyi; V. Y. Skorokhoda (The State Expert Center of the Ministry of Health of Ukraine, 2022)
Drug-loaded films are of great interest among fast-dissolving drug-delivery systems. The creation of fast-dissolving films for the treatment of cardiovascular diseases is important.The first inhibitor of angiotensin-converting enzyme to appear on the world market was captopril, which is used to treat hypertension, chronic heart failure and others. Captopril has an antihypertensive effect, which manifests itself within 5-15 minutes after sublingual administration. The aim of our study was to develop the technology of captopril fast dissolving films by solvent casting method and analyze the influence of groups of excipients on technological properties of the films. The influence of the character of polymers, plasticizers, disintegrants and sweeteners on the technological properties of experimental batches of captopril fast dissolving films was studied. Such technological indicators as uniformity of weight, thickness, swelling index,tensile strength, elongationand disintegration time were studied. The influence of excipients' composition on the technological indicators of captopril fast dissolving films has been researched. It was found out that the effect of the type of polymer had the decisive influence on all parameters of films.The selected plasticizer determined the elasticity (films' elongation), film thickness and weight variation. Optimal values of the average weight and thickness of captopril films are provided by the use of a polymer in the combination of HPMC with PEG 4000 or a combination of HPMC with PEG 6000, as a plasticizer - glycerin or PEG 400. The best results of films' swelling were obtained with the introduction of HPMC brands Metolose® 90 SH 100 000 or Metolose® 65 SH 50, Polyplasdone XL-10 crospovidone, propylene glycol and sorbitol. The disintegration time less than 3 min was observed in all investigated film compositions, except those containing PVA. The highest value of tensile strength for captopril films was obtained using HPMC brand Metolose® 65 SH 50 or Metolose®90 SH 100 000. Using the desirability function, the optimal excipients within the studied groups were selected.It has been established that the optimal values of the technological parameters of captopril films can be achieved using Hydroxypropyl MethylcelluloseVivapharm® E15, polyethylene glycol 400, sodium starch glycolate and sorbitol.